1999
DOI: 10.1192/bjp.174.6.500
|View full text |Cite
|
Sign up to set email alerts
|

Durability of the effects of cognitive–behavioural therapy in the treatment of chronic schizophrenia: 12-month follow-up

Abstract: At 12-month follow-up the significant advantage of cognitive-behavioural therapy compared to routine care alone remained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(92 citation statements)
references
References 7 publications
2
86
0
4
Order By: Relevance
“…However, delayed or enduring effects have not been observed in other studies (Tarrier et al 1999, and the most recent meta-analysis (NICE, 2008) found effect sizes for CBT against ' active controls ' (mainly non-specific control interventions, but in one case cognitive remediation therapy) of only x0.18 (95 % CI x0.39 to +0.03, five studies) at 12-month follow-up and x0.08 (95 % CI x0.40 to +0.24, three studies) at 24 months.…”
Section: Study (1st-named Author)mentioning
confidence: 73%
“…However, delayed or enduring effects have not been observed in other studies (Tarrier et al 1999, and the most recent meta-analysis (NICE, 2008) found effect sizes for CBT against ' active controls ' (mainly non-specific control interventions, but in one case cognitive remediation therapy) of only x0.18 (95 % CI x0.39 to +0.03, five studies) at 12-month follow-up and x0.08 (95 % CI x0.40 to +0.24, three studies) at 24 months.…”
Section: Study (1st-named Author)mentioning
confidence: 73%
“…Four studies 61,[70][71][72] delivered cognitive therapy during the acute/recovery phase. Three studies 65,73,74 focused on those with drug-resistant symptoms. One study 75 studied group cognitive therapy.…”
Section: Schizophreniamentioning
confidence: 99%
“…The BPRS was employed in the studies by Buchkremer and colleagues, 76 Garety and colleagues, 73 Haddock and colleagues, 70 Startup and colleagues 72 and Tarrier and colleagues. 74 The CPRS was used in the study by Sensky and colleagues. 65 The PANSS was used in the studies by Barrowclough and colleagues 68 and Lewis and colleagues.…”
Section: Schizophreniamentioning
confidence: 99%
“…Sensky et al (2000) found that the CBT group continued to improve on measures of positive symptoms, depression and negative symptoms. Tarrier et al (1999) reported 12-month follow-up results for CBT compared to supportive counselling (SC) or routine care (RC). Participants in CBT continued to show significant treatment effects for both positive and negative symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Four trials provide post-treatment follow-up (Kuipers et al 1998 ;Drury et al 2000 ;Sensky et al 2000;Tarrier et al 1999Tarrier et al , 2000. Kuipers et al (1998) and Sensky et al (2000) do not report relapse rates for their participants.…”
Section: Introductionmentioning
confidence: 99%